2005
DOI: 10.1002/ejoc.200400634
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of 3‐Hydroxydrimanes Mediated by Titanocene(III) – Evaluation of Their Antifeedant Activity

Abstract: We describe the first synthesis of 3β-hydroxydihydroconfertifolin (3) and 3β-hydroxycinnamolide (4), together with improved procedures for the preparation of other 3-hydroxydrimanes (2 and 5) scarce in nature. The key step was the titanocene(III)-promoted cyclization of epoxypolyprenes, readily prepared from commercial polyenes. In this way, we confirm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 44 publications
0
13
0
1
Order By: Relevance
“…[62,63] Oral cannulation of S. littoralis L6 larvae showed that the non-fluorinated derivatives 19 and 51 were moderate post-ingestive antifeedants whereas the fluorinated derivative of 19 (i.e., 11) was toxic (pANCOVA2 Ͻ 0.05, see the Supporting Information). Post-ingestive effects against this insect have been reported for 3β-hydroxycinnamolide and 3β-acetoxydrimenin [64] and suggested for synthetic analogues (lactones) of polygodial (6) and warburganal (7) on Pieris brassicae and L. decemlineata larvae. [63] However, 6 did not affect orally injected S. littoralis.…”
Section: Evaluation Of Antifeedant Activitymentioning
confidence: 97%
“…[62,63] Oral cannulation of S. littoralis L6 larvae showed that the non-fluorinated derivatives 19 and 51 were moderate post-ingestive antifeedants whereas the fluorinated derivative of 19 (i.e., 11) was toxic (pANCOVA2 Ͻ 0.05, see the Supporting Information). Post-ingestive effects against this insect have been reported for 3β-hydroxycinnamolide and 3β-acetoxydrimenin [64] and suggested for synthetic analogues (lactones) of polygodial (6) and warburganal (7) on Pieris brassicae and L. decemlineata larvae. [63] However, 6 did not affect orally injected S. littoralis.…”
Section: Evaluation Of Antifeedant Activitymentioning
confidence: 97%
“…Thus, a reaction of epoxide 16 (epimer mixture) with Cp 2 TiCl 2 (2.5 equiv) and Mn (8 equiv) in the absence of H 2 O 23 resulted in the formation of aldehyde epi-17 as a single diastereomer in 50% yield, 24 along with allylic alcohol 18 in 14% yield. 25 In conclusion, we achieved synthesis of the key sesquiterpene intermediate 2 bearing all requisite stereocenters of sespendole (1). The synthetic features involved (1) highly stereoselective [2,3]-Wittig rearrangement to obtain the C3 quaternary stereogenic center in the densely functionalized substrate and (2) isomerization of the epoxide with a low-valent titanium reagent without H 2 O in a highly stereoselective manner.…”
Section: Scheme 3 Construction Of C3-quaternary Carbon Center Throughmentioning
confidence: 98%
“…402 However, the lack of correlation between reactivity towards nucleophiles and the antifeedant effects of polygodial and warburganal suggests that their insect antifeedant action may depend on other properties as indicated by the activity of keto-aldehydes and 3-hydroxydrimanes. 403 The potential of the sesquiterpenes present in Senecio species as natural crop protectant lead have recently reported. 404 These species are characterized by their content in sesquiterpenes with eremophilane, cacalol, bisabolane, silphinene, caryophillane, humulane, germacrane and benzofurane skeletons.…”
Section: Sesquiterpenesmentioning
confidence: 99%